Analysing street heritage trees surface temperature for UHI mitigation using remote sensing and GIS application / Nor Suhaida Yusof, Nur Huzeima Mohd Hussain and Noradila Rusli - Nor Suhaida, Yusof; Nur Huzeima, Mohd Hussain; Noradila, Rusli (Universiti Teknologi MARA, Perak, 2019)
Urban Trees are important in reducing the heat by providing the shade and cooling effect to the urban environment. Every tree species provides different cooling effect depending on their tree characteristics. Evergreen species such as heritage tree are significant in reducing the surface temperature. In particular, heritage trees do have environmental implications which provide lots of benefits for the environment and human health. The aim of this paper is to analyse the heritage trees surface temperature in mitigating urban heat island (UHI) at Taiping Old Town. The research has conducted utilizing Landsat 8 OLI data and on-site data collection. This research integrated Geographic Information System (GIS) and remote sensing in data processing and SPSS for analysis. The result shows the low significant relationship of tree characteristics and Land Surface Temperature (LST) with (R²=0.17) indicates that external factors can reduce the cooling effect from heritage trees in reducing the surface temperature in the urban area. Moreover, there is also an analysis on the LST of land cover features together with the frequency of heritage trees. The findings revealed that the higher frequency of heritage trees planted at the hard surface; the higher the ability to reduce the LST (about 5.3°C) in urban areas.